Penerapan Kebijakan Harga Transfer Bahan Baku Untuk Pengukuran Prestasi Divisi Pada PT. Honoris Industry - Pamungkas, Bambang; Yuliati, Nunuk (Sekolah Tinggi Ilmu Ekonomi Kesatuan, 2008)
In a big company, where there is more and more longer process of production, usually the main functional activities are carried out by separated organization unit named division. If a division buys basic commodity from other division in the same company, transfer price need to be fixed. It is not easy to fix transfer price. The purpose of this research is to find out transfer price policy application of basic commodity in behalf of division performance measurement at PT Honoris Industry Bogor. The outcome of this research shows that transfer price fixation utilized by the company to electronic division and camera division is cost plus method, namely standard variable cost plus mark up 30%. This transfer price must be fixed by top management, in this case is production director. Division manager has only right to propose the best price. The fixation of accurate method can be as a way of division performance measurement. The principle of performance evaluation conducted to both of the divisions encompasses: (a) periodical profit, (b) product quality, and (c) production efficiency. Keywords: Transfer price fixation; Basic commodity; Performance measurement;